Proceedings of the XLII Technical and Scientific Congress of the Portuguese Association of Swimming Technicians - Aldo Matos da Costa; Ana Teresa Conceição; Mário Jorge Costa; Nuno Domingos Garrido (Desafio Singular, 2019)
The abstracts published in the present supplement were submitted to the Scientific Committee of the XLII Technical and Scientific Congress of the Portuguese Association of Swimming Technicians - APTN held on 26 to 28th of April of 2019 in the city of Portimão. The content of the articles is solely and exclusively the responsibility of their authors. The APTN Scientific Committee assumes no responsibility for the opinions and statements expressed by the authors. Partial reproduction of the texts and their non-commercial use is permitted, provided the source/reference is duly cited.